1997
DOI: 10.1002/eji.1830270317
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of I‐309 gene expression in human monocytes by endogenous interleukin‐1

Abstract: Activated human monocytes are a source of numerous beta-chemokines. The present study was conducted to determine whether these cells produce the human beta-chemokine I-309 and to compare the induction requirements of I-309 to those of other beta-chemokines. We demonstrate that appropriately stimulated adherence-purified human peripheral blood monocytes express I-309 transcripts and secreted I-309 protein. Two stimuli, immobilized IgG and lipopolysaccharide (LPS), synergize strongly to induce I-309 gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 39 publications
2
27
1
Order By: Relevance
“…CCL1 has previously been reported to be produced from activated T lymphocytes, in particular Th1 effector cells, as well as IgG-and LPS-activated monocytes (35,36). However, our data would suggest that mast cells are the predominant cellular source of CCL1, expressing CCL1 mRNA at levels 100-fold higher than in T lymphocytes and monocytes in vitro.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…CCL1 has previously been reported to be produced from activated T lymphocytes, in particular Th1 effector cells, as well as IgG-and LPS-activated monocytes (35,36). However, our data would suggest that mast cells are the predominant cellular source of CCL1, expressing CCL1 mRNA at levels 100-fold higher than in T lymphocytes and monocytes in vitro.…”
Section: Discussioncontrasting
confidence: 71%
“…Sections were hybridized with cRNA probes that were constructed from cDNA coding for CCR8 and CCL1 using standard method (29). Briefly, the probes were labeled with S 35 or digoxigen-UTA in the presence of SP6 and T7 polymerase. Following hybridization, the mRNA-cRNA signal was developed.…”
Section: Ccr8 and Ccl1 In Situ Hybridizationmentioning
confidence: 99%
“…Their enhanced expression during inflammatory processes is stimulated by different cytokines in various cell types, i.e., by IL-1, TNF-␣, and IFN-␥ in human airway smooth-muscle cells (12), by IL-1 and IFN-␥ in both fibroblasts and epithelial cells (13) and by endogenous IL-1 in monocytes (14).…”
mentioning
confidence: 99%
“…Upon activation, CCL1 is produced by a number of cellular sources, including peripheral blood mononuclear cells, monocytes, activated T-lymphocytes and endothelial cells [8,13,14]. In vitro studies have shown that CCL1 as well as both CCL22/ monocyte-derived chemokine (MDC) and CCL17/ thymus-and activation-regulated chemokine (TARC) induce migration of lymphocytes, especially of the Th2 phenotype [13,14]. CCL22 and CCL17 activate these cells through the CC chemokine receptor (CCR)4, whereas CCL1 uses CCR8 [15,16].…”
mentioning
confidence: 99%